Refiguring modernism. - Scott, Bonnie Kime, 1944- (Indiana University Press, 1995)
A revisionist study of modernism, which draws on close analysis of the strategic writing processes of Virginia Woolf, Rebecca West, and Djuna Barnes to show how each writer negotiated modernist questions of enduring importance to postmodern readers. It closes with a consideration of the ends of modernism, assessing the volatile politics of 1939.